2011
DOI: 10.1007/s12630-011-9625-0
|View full text |Cite
|
Sign up to set email alerts
|

Remifentanil versus fentanyl for intravenous patient-controlled labour analgesia: an observational study

Abstract: Purpose We undertook a retrospective study to compare the analgesic efficacy and effects on neonatal outcome of administering either remifentanil or fentanyl intravenous patient-controlled analgesia (IVPCA) during labour. Methods A five-year retrospective cohort study was undertaken of women with more than 24 weeks of gestation who had received either IVPCA remifentanil or fentanyl for labour analgesia at Mount Sinai Hospital. The sampling timeframe was from November 2005 to March 2010. The standard IVPCA regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 35 publications
3
28
1
2
Order By: Relevance
“…This supports recommendations to administer supplementary oxygen to all women using remifentanil PCA [13,15,17,18], but also reinforces the need for highquality protocols and midwifery training for remifentanil PCA.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…This supports recommendations to administer supplementary oxygen to all women using remifentanil PCA [13,15,17,18], but also reinforces the need for highquality protocols and midwifery training for remifentanil PCA.…”
Section: Discussionsupporting
confidence: 72%
“…We found that 70% of women underwent at least one desaturation episode when using remifentanil PCA. This is higher than incidences between 0% and 24% reported by other studies using the same threshold to define desaturation [8][9][10][11][12][13][14][15]. In these studies, oxygen saturation was recorded intermittently or relied upon study personnel to document desaturation episodes manually.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Typically described is initial decrease in the intensity of labour pain during the first hour following remifentanil and then a return of pain intensity to initial values , even using a different application method and dose 14,15,29,31,32 . Despite this course, surprisingly few subsequent applications of epidural analgesia are described for inadequate pain relief using remifentanil (0-10%) which is hard to explain from the published data 28,29,[33][34][35] .…”
Section: Safety and Efficacy Of Remifentanil In Labourmentioning
confidence: 99%
“…En una serie de 23 neonatos no se observaron diferencias hemodinámicas ni en la saturación de oxígeno en las primeras 24 horas de vida tras recibir las madres una PCA de remifentanilo, aunque los autores describen durante la primera hora una tendencia a la hipotensión respecto a los neonatos cuyas madres no recibieron remifentanilo 83 . Comparado con la petidina, los resultados de los test neuroconductuales de los neonatos cuyas madres recibieron remifentanilo fueron mejores 66 y con el fentanilo, la incidencia de reanimación neonatal menor 84 . Las dosis usadas en la PCA varían de bolos de 0,15 a 0,5 μg/kg (rango 0,15 a 0,93 μg/kg) infundidos en 20 seg con intervalo de bloqueo de 1-3 min 85,86 .…”
Section: Opioidesunclassified